Legal Responsibility of Healthcare Facilities in the Management of Medical Emergencies - Sakinatunnisa, Silvi; Alawiya, Nayla (LPPM Universitas Harapan Bangsa, 2025)
The legal responsibility of healthcare facilities in providing emergency services is a crucial element in safeguarding the public's right to health. This study aims to analyze the forms of legal responsibility and the synchronization of regulations concerning the obligations of healthcare facilities in managing medical emergencies. The research method employed is normative juridical, using statutory, conceptual, and analytical approaches. The data is based on primary and secondary legal materials, analyzed through normative qualitative methods using systematic, grammatical, and teleological interpretations. The findings show that the regulation of legal responsibility demonstrates both vertical and horizontal synchronization, especially between Law No. 17 of 2023 on Health, government regulations, and various ministerial decrees. Legal responsibility is divided into two main categories: criminal liability under Article 438 of Law No. 17 of 2023 and administrative liability as stipulated in Ministerial Regulation No. 4 of 2018 and Ministerial Regulation No. 9 of 2014. However, regulatory gaps remain, particularly in rules concerning independent practices and community health centers that do not explicitly mandate emergency care obligations. Therefore, harmonization and legal reform are needed to strengthen the protection of patients in emergency conditions.